Positive Character Education Values Found in Simba, The Lion King (1994) Movie - Piscayanti, K. S.; Suprianti, G.A.P.; Premana, M.Y.H. (Journal of Education Research and Evaluation, 2020)
Motion pictures or movie is highly related with someone’s daily life that easily to be obtained by almost most of the people. Additionally, movie can deliver ideas, experiences, and ways of thinking through visual and sound which offered by the film that engages spectators’ minds and emotions. This study aimed to analyze the values of character education on Simba in The Lion King (1994) movie. This study was a descriptive qualitative study in which textual analysis was used in order to analyse the data where the data in the form of movie was treated like a text and analysed in the cycling process in order to obtain the dependable data. The result of this study showed that The Lion King (1994) contained all values of character education which stated by Ministry of Education and Culture. Those values were showed in different timing where in the beginning of the movie there were 9 characters namely; religious, tolerant, discipline, autonomous, hardworking, cooperative, solidary, responsible, and honest, while in the middle part of the movie there were 11 characters, namely; sincere, nature loving, peace loving, patriotic, creative, resilient, appreciative, integrity, loyal, inclusive, and nationalistic. This result proves that The Lion King (1994) movie is a good movie for children which is suitable to be used in learning purposes.